Implementation of STEM-Integrated Project-Based Learning Tools Based on Local Content (Jambi Coffee) to Improve Student Learning Outcomes - Amanda, Putri; Pathoni, Haerul; Amnie, Erlida (Lensa: Jurnal Kependidikan Fisika, 2025)
This study aimed to investigate the effectiveness of Project-Based Learning (PjBL) tools integrated with STEM and local content—specifically the cultural practice of Jambi coffee brewing—in enhancing students’ learning outcomes in the physics topic of temperature and heat. The research employed a quasi-experimental method using a non-equivalent control group design. The participants were 11th-grade students from SMA Negeri 11 Muaro Jambi in the 2024/2025 academic year, selected through purposive sampling. A total of 54 students participated, divided evenly into two classes: the experimental class, which was taught using STEM-integrated PjBL tools incorporating local content, and the control class, which was taught using conventional PjBL tools without STEM or local context integration. Both groups underwent pretest and posttest assessments. Data were analyzed using paired sample t-tests and independent sample t-tests with a significance level of 0.05. The paired t-test results indicated a statistically significant improvement in both classes (p = 0.000). However, the independent sample t-test revealed a significant difference in posttest scores between the two groups (p = 0.011), with the experimental class showing greater gains. These results suggest that the integration of STEM and local cultural context into PjBL can deepen students’ conceptual understanding, enhance engagement, and improve learning outcomes more effectively than PjBL alone. The contextualization of physics content using familiar real-world practices, such as coffee brewing, provides meaningful learning experiences that connect abstract scientific concepts to students' daily lives.